Emergency Medical Management for Education Innovative Applications in Dealing with Tsunami Disasters - Bachri, Syamsul; Prastyo, Alfian Eko; Harsono, Yudi Tri; Akbar, Muhammad Iqbal; Rahman, Khaidir (International Journal of Interactive Mobile Technologies (iJIM), 2021)
In 2018 until 2019 there were three events, namely tsunamis in Banten, Lampung and Central Sulawesi Provinces. The total death toll in the tsunami reached 3,754 and the number of victims suffering injuries amounted to 18,493 (BNPB, 2019). One effort that can be implemented to minimize this impact is to develop an Android-based emergency medical disaster response application for Communities Residing in Tsunami Prone Areas. The application was developed with several stages, namely emphatize, define, ideate, prototype, testing. The emphatize stage includes interviews and gathering information about problems that occur in the field. The define stage includes formulating problems that occur in the field and trying to solve those problems with solutions. At the Ideate stage the system architecture is designed using UML design and User Interface design. Furthermore, a prototype design was made which was adjusted to the results of the analysis carried out in the previous stage. The testing phase includes the results of the test material, Usability and Functionality Suitability shows that the application of emergency medical disaster response received the title "Very Eligible" to be implemented in communities in areas prone to tsunami natural disasters. With the breakdown of the Usability testing results reached 86.3%, and the Functionality Suitability testing reached 100%, and the material test results reached 100%. This application use for improving an education Tsunami disaster response based on problem and creative thinking.